The kings and the pawns : collaboration in Byelorussia during World War II - Rein, Leonid (War and genocide, 2011)
"For many years, the history of Byelorussia under Nazi occupation was written primarily from the perspective of the resistance movement. This movement, a reaction to the brutal occupation policies, was very strong indeed. Still, as the author shows, there existed in Byelorussia a whole web of local institutions and organizations which, some willingly, others with reservations, participated in the implementation of various aspects of occupation policies. The very sensitivity of the topic of collaboration has prevented researchers from approaching it for many years, not least because in the former Soviet territories ideological considerations have played an important role in preserving the topic's 'untouchable' status. Focusing on the attitude of German authorities toward the Byelorussians, marked by their anti-Slavic and particularly anti-Byelorussian prejudices on the one hand and the motives of Byelorussian collaborators on the other, the author clearly shows that notwithstanding the postwar trend to marginalize the phenomenon of collaboration or to silence it altogether, the local collaboration in Byelorussia was clearly visible and pervaded all spheres of life under the occupation"--Provided by publisher.